Happiness from rural experience in Dalmatia: exploring the role of tourist mindfulness as moderator - Loureiro, S. M. C.; Breazeale, M.; Radic, A. (Journal of Vacation Marketing, 2019)
The present study aims to analyze (i) the effect of mindfulness as a moderator on the relationship between rural experience economy and happiness and (ii) the influence of rural experience, specifically agritourism, on behavioral intentions through happiness and memory creation. The relationships hypothesized in the model are informed by a literature review and tested using partial least squares approach and bootstrapping procedure. Data are collected in Dalmatia (Croatia) from nearby rural tourists who stayed at agritourism accommodations. The results suggest that (i) rural tourism experience dimensions are positively and significantly associated with happiness; (ii) mindfulness does not fully influence the strength or direction of the relationship between the rural experience and happiness; and (iii) happiness and memory can act as mediators, at least partially, between rural tourism experience and happiness. The findings provide theoretical and managerial implications for tourism and hospitality.